A Red Wallflower - Warner, Susan, 1819-1885 (Salt Lake City, UT : Project Gutenberg, 2008)
"A Red Wallflower" by Susan Warner is a novel written in the late 19th century. The story follows Colonel Gainsborough, a retired army officer who relocates to a small Connecticut village with his wife and young daughter, Esther. Following Mrs. Gainsborough's death, the narrative focuses on Esther's relationship with her father and the budding friendship with a young man named Pitt Dallas, as they navigate themes of grief, education, and the search for companionship. At the start of the novel, we are introduced to the Gainsborough family, grappling with the loss of the mother figure, which has left both Colonel Gainsborough and Esther in a state of mourning and isolation. The opening chapters depict their quiet lives in New England, where Colonel Gainsborough's aloofness and increasing sadness deeply affect his daughter, who yearns for connection and understanding. A chance friendship with Pitt Dallas revitalizes Esther's spirits, bringing her a sense of purpose as he becomes her tutor and confidant, but the shadows of grief and the complexity of their lives loom large as the story unfolds. (This is an automatically generated summary.)
Release date is 2008-10-07
Produced by Daniel Fromont
Keywords: Fiction